The performance of a field scale biofiltration cells in reducing nutrient rich surface runoff from an informal settlement in South Africa - Mgese, Sivile (Department of Environmental and Geographical Science, 2024)
Concerns about the deterioration of water quality are exacerbated by the effects of rapid and unplanned urbanisation in South African urban catchments as the number of informal settlements next to watercourses increase. Residents living in nonsewered informal settlements typically discard their household greywater, solid waste and blackwater into makeshift drainage conduits which find their way into receiving water bodies. This study examined the ability of Nature based Solutions (NbS) as a viable option to treat and reduce elevated nutrient concentrations discharged from informal settlements. Currently, there is limited knowledge and understanding about the performance of NbS in treating and reducing nutrient rich surface runoff with associated sediments that originates from informal settlements. This thesis contributes to the application and understanding of the novel NbS scientific body of literature on water treatment, firstly by utilising field scale biofilter cells to mitigate the impact of elevated nutrient concentrations from an informally settled catchment; and secondly, to recover, and assess the risk of reusing treated water for irrigation of food gardens in a food insecure and water scarce South Africa. The field scale biofilter cells were positioned at an abandoned Wastewater Treatment Works (WWTW) downstream of the non-sewered informal settlement in Franschhoek, South Africa. The biofilter cells consisted of six purpose-built cells that were filled with various substrate media selected for their ability to treat and reduce nutrient concentrations. This was to compare the efficacy of each biofilter cell in the treatment and reduction of concentrations under different Hydraulic Residence Time (HRT) and flow rates. Linear regression was used to measure the effectiveness of each substrate in the biofilter cells and to evaluate the change in cell performance over time against the influent feedstock. A one-way ANOVA was used to compare the means of the biofilter cells over the sampling period to ascertain the best treatment cell. The Large Stone Vegetated (LSV) biofilter cell was one of the best performing cells for treatment and reduction of PO4 3- concentrations with the lowest median (0.26 mg/L), mean (0.71 mg/L) and 95th percentile (3.60 mg/L), against influent mean, median and 95th percentile concentrations of 3.18 mg/L, and 2.86 mg/L and 5.61 mg/L respectively.